Improving Access to Safe Drinking Water in a Rural Government School in Haryana: A Public Health Case Report - Udita Singh; Vats Sabharwal; Kanta Sabharwal (Journal of Public Health and Primary Care, 2026)
Abstract Access to safe drinking water remains a challenge in many rural schools in India, adversely affecting child health and educational outcomes. This case report describes a field-based intervention in a government school in Palwal district, Haryana, where lack of safe drinking water was associated with frequent episodes of diarrheal illness and school absenteeism among students. Through intersectoral collaboration involving school authorities, Krishi Vigyan Kendra, and a public health practitioner, a water purification and storage facility was installed, and water, sanitation, and hygiene awareness sessions were conducted. Following the intervention, a marked reduction was observed in reported diarrheal episodes, and improvements in student attendance and classroom engagement were observed. This case highlights the importance of simple, context-specific interventions and intersectoral coordination in addressing basic public health needs in underserved settings.